Comparison of Postoperative Sensitivity between Bulk-Fill Composite Restoration and Conventional Composite Restoration, Randomized Controlled Trial - Awan, Tahir; Ahmed, Alia; Azhar, Muhammad Daniyal (Biological and Clinical Sciences Research Journal, 2025)
Postoperative sensitivity is a common concern following composite resin restorations, particularly in posterior teeth. Differences in restorative techniques, such as the use of conventional versus bulk-fill composites, may influence patient-reported sensitivity. However, evidence comparing these two approaches remains limited. Objective: To compare the frequency of postoperative sensitivity to thermal stimuli (hot and cold) in Class I posterior cavities restored with conventional composite resin versus bulk-fill resin composite. Methods: This randomized controlled trial was conducted at the Department of Operative Dentistry, Islamic International Dental College/Hospital, Islamabad, from September 30, 2024, to March 29, 2025. A total of 270 teeth were included and randomly allocated into two equal groups: Group A (n=135) received conventional composite restorations, and Group B (n=135) received bulk-fill resin composite restorations. Participants aged 20–60 years of either gender were enrolled using a non-probability purposive sampling technique. Postoperative sensitivity to thermal stimuli (hot and cold) was assessed, and data were analyzed using appropriate statistical tests with a significance level set at p < 0.05. Results: Group A had a mean age of 39.53 ± 11.60 years, and Group B had a mean age of 42.47 ± 11.63 years. In Group A, 6 patients (4.4%) reported postoperative sensitivity to hot stimuli, compared to 9 patients (6.7%) in Group B (p = 0.425). Sensitivity to cold stimuli was observed in 3 patients (2.2%) in Group A and 9 patients (6.7%) in Group B (p = 0.076). The differences between the two groups were not statistically significant. Conclusion: There was no statistically significant difference in postoperative sensitivity to thermal stimulation between Class I posterior restorations completed with bulk-fill composite resin and those restored using conventional composite resin. Both materials appear comparable in terms of short-term thermal sensitivity outcomes.